The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/suco.201800078
|View full text |Cite
|
Sign up to set email alerts
|

Structure, performances, and formation mechanism of cement composites with large‐scale regular microstructure by distributing uniformly few‐layered graphene oxide in cement matrix

Abstract: The multiple layered graphene oxide (GO) was prepared by modified Hummer's method. Then few-layered GO was obtained by forming intercalation composites with the multiple layered GO and poly(acrylic acid-acrylamide-diallyl dimethyl ammonium chloride) (PAAD). The goal is to prepare large-scale ordered structure in the whole cement composites by distributing uniformly the GO in cement matrix. The effects of PAAD on GO nanosheets and its distribution within the cement paste were investigated and assessed by charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…In addition, the calcium hydroxide in the CCG paste exhibits a relatively dense petal shape. The mechanism through which the petal-like crystals are formed indicates that regular crystals are formed by the template effects of the GO and the ordered structures are formed by the interweaving and crosslinking caused by the crystal growth [32]. It can be inferred that the pore structure of the CCG hydration product is denser than that of the blank paste.…”
Section: The Influence Of the Go On The Chemical Shrinkage Behaviour mentioning
confidence: 99%
“…In addition, the calcium hydroxide in the CCG paste exhibits a relatively dense petal shape. The mechanism through which the petal-like crystals are formed indicates that regular crystals are formed by the template effects of the GO and the ordered structures are formed by the interweaving and crosslinking caused by the crystal growth [32]. It can be inferred that the pore structure of the CCG hydration product is denser than that of the blank paste.…”
Section: The Influence Of the Go On The Chemical Shrinkage Behaviour mentioning
confidence: 99%
“…Esse melhor ordenamento ocorre através dos planos de GO em interação com os íons de cálcio, que atuam como ponto inicial de crescimento dessas fases cristalinas. Em virtude disso, observou-se o melhor desempenho mecânico pela matriz [36]. Já nas adições superiores a 0,30%, acredita-se que o as unidades de GO façam interação entre si formando agregados de GO, devido ao excesso da nanopartícula em suspensão.…”
Section: Figuraunclassified
“…The authors attributed this phenomenon to the results of the porosity measurements, i.e., to the significant refinement of large capillary pores. 16 As a consequence, the decreased mobility of chloride and sulfate ions within cement matrix 16,23 as well as the improved performance of cement composites during freeze-thaw cycles 19,20 and carbonation tests 19,20,22 have been reported in several studies. Similarly, comparable results have been obtained for GNP-cement composites revealing a significantly reduced water penetration depth, even by 75%, 5,21 accompanied by an increased chloride migration resistance.…”
mentioning
confidence: 95%
“…Most importantly, it has been reported that the addition of GO notably reduces the sorptivity of cement composites. [15][16][17][18][19][20] The maximum reduction of 46% 18 and 44% 15 has been quantified for initial and secondary sorptivity, respectively, if compared to plain composites. The authors attributed this phenomenon to the results of the porosity measurements, i.e., to the significant refinement of large capillary pores.…”
mentioning
confidence: 99%